A virtual lymph node model to dissect the requirements for T‐cell activation by synapses and kinapses. Issue 7 (10th May 2016) - Moreau, Hélène D; Bogle, Gib; Bousso, Philippe
Abstract : The initiation of T‐cell responses in lymph nodes requires T cells to integrate signals delivered by dendritic cells (DCs) during long‐lasting contacts (synapses) or more transient interactions (kinapses). However, it remains extremely challenging to understand how a specific sequence of contacts established by T cells ultimately dictates T‐cell fate. Here, we have coupled a computational model of T‐cell migration and interactions with DCs with a real‐time, flow cytometry‐like representation of T‐cell activation. In this model, low‐affinity peptides trigger T‐cell proliferation through kinapses but we show that this process is only effective under conditions of high DC densities and prolonged antigen availability. By contrast, high‐affinity peptides favor synapse formation and a vigorous proliferation under a wide range of antigen presentation conditions. In line with the predictions, decreasing the DC density in vivo selectively abolished proliferation induced by the low‐affinity peptide. Finally, our results suggest that T cells possess a biochemical memory of previous stimulations of at least 1–2 days. We propose that the stability of T‐cell–DC interactions, apart from their signaling potency, profoundly influences the robustness of T‐cell activation. By offering the ability to control parameters that are difficult to manipulate experimentally, the virtual lymph node model provides new possibilities to tackle the fundamental mechanisms that regulate T‐cell responses elicited by infections or vaccines.